The Distributional Consequences of Social Distancing on Poverty and Labour Income Inequality in Latin America and the Caribbean - Isaure Delaporte; Julia Escobar; Werner Pe\~na (Global Labor Organization (GLO), 2020)
This paper evaluates the distributional consequences of social distancing due to the COVID-19 pandemic on poverty and labour income inequality in 20 Latin American and Caribbean (LAC) countries. We gather detailed information from national laws and decrees on the strictness and the duration of the lockdown in each country and use rich harmonised household surveys from the IADB. We estimate the share of individuals that are potentially able to remain active under the first phase of the lockdown by constructing the Lockdown Working Ability (LWA) index which takes into account individuals' ability to work from home but also whether their occupation is affected by workplace closures or mobility restrictions. We find that, on average, 1 worker out of 2 is able to work under the lockdown in the LAC region. We document considerable variation in the share of individuals able to work under the lockdown across countries and within countries across occupations, economic activities and specific population groups. Based on the LWA index, we then estimate individual's potential labour income losses and examine changes in poverty and labour income inequality. We find an increase in poverty and labour income inequality in the majority of the LAC countries due to social distancing. At the national level, the highest increase in the headcount poverty index is 1.4 pp and the highest increase in the Gini coefficient is 2 pp. Decomposing overall labour income inequality in the LAC region, we find that social distancing has lead to a small decrease (-0.1 pp) in inequality between countries but to an increase (2 pp) in inequality within countries. Finally, we document that 63% of the dispersion in the labour income loss across countries is explained by the sectoral/occupational structure of the economies, while the rest is explained by the type of lockdown policy that was implemented.
Keywords: D33; E24; I14; J31; J21; 330; COVID-19; Social Distancing; Teleworking; Employment; Labour Income Inequality; Poverty